2015
DOI: 10.1016/j.jeap.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Furthering and applying move/step constructs: Technology-driven marshalling of Swalesian genre theory for EAP pedagogy

Abstract: John Swales' seminal work has inspired a wealth of research with important pedagogical implications for genre-based writing instruction. Continuing the prolific move analysis tradition in EAP research, this article presents empirically devised and validated cross-disciplinary IMRD move/step frameworks for the research article genre and demonstrates how Swales' move and step concepts underlying these frameworks formed the foundation of innovative genre-based automated writing evaluation technology. Overall, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 54 publications
0
53
0
3
Order By: Relevance
“…For example, Cotos et al. () retrieved high‐probability n ‐grams representative of each move and step in various disciplines and used them for the Research Writing Tutor technology. This suggests that n ‐grams can be used to identify linguistic realizations of moves and steps, because they allow commonly occurring keywords, phrases, and discourse markers to be detected (Anthony & Lashkia, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Cotos et al. () retrieved high‐probability n ‐grams representative of each move and step in various disciplines and used them for the Research Writing Tutor technology. This suggests that n ‐grams can be used to identify linguistic realizations of moves and steps, because they allow commonly occurring keywords, phrases, and discourse markers to be detected (Anthony & Lashkia, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of their study suggested that the Mover could be used to help users, particularly L2 scientists and engineers, better understand and construct research papers in different fields and disciplines. Another recent development in the automated move-based technologies is the Research Writing Tutor, developed by Cotos (2014Cotos ( , 2016 and her colleagues (Cotos, Huffman, & Link, 2015). The Research Writing Tutor is a pedagogical tool for teaching and learning disciplinary research article writing, which aims to advance genre-based writing instruction to the next level by incorporating an automated writing evaluation program (i.e., the Research Writing Tutor identifies move and step boundaries automatically and uses them as criteria for automated feedback).…”
Section: Corpus Use In Genre-based Writing Pedagogymentioning
confidence: 99%
See 2 more Smart Citations
“…Our methodology is described in detail in Cotos, Huffman, and Link (2015); here, we summarize it in Figure 1. In short, we first conducted an inductive analysis and pilot annotation of a sample of 150 texts (5 from each discipline), and that resulted in specific move and step descriptors, which were refined based on the feedback provided by the disciplinary consultants.…”
Section: Corpus-based Move Analysismentioning
confidence: 99%